Genetic Variability, Correlation and Path Coefficient Studies in Elephant Foot Yam (Amorphophallus campanulatus Bl.) (Journal of Scientific Research, 2013)
An investigation has been made to characterize the local accessions of Elephant foot yam collected from thirteen aroid growing districts and in-depth study on genetic variability, correlation and path coefficient for plant height, petiole length, petiole breadth, leaf area index, corm length, corm breadth, corm weight, cormel number, cormel length, cormel breadth, cormel weight and yield per plant has also been carried out. Genotypic variances and coefficient of variation for most of the characters were remarkably higher than their corresponding environmental variances, which also indicate the existence of variation in genotypic origin. High heritability with high genetic advance in percentage of mean was also observed for all characters. In the correlation study plant height, leaf area index, corm length, corm breadth, corm weight, cormel number, cormel length, cormel breath showed positive correlation with yield per plant in genotypic and phenotypic level. Leaf area index, cormel number in phenotypically and cormel number in genotypic level showed relatively high positive direct effect on yield per plant.Keywords: Amorphophallus; Genetic variability; Correlation; Path coefficient.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.13853        J. Sci. Res. 5 (2), 371-381 (2013)